Aquatic disease in New Zealand: synthesis and future directions. Issue 1 (2nd January 2022) - Lane, Henry S.; Brosnahan, Cara L.; Poulin, Robert
ABSTRACT: Dedicated studies on aquatic disease in New Zealand began in 1974, inspired by a developing aquaculture industry. Since then, two main aquatic disease study areas have emerged: (1) aquatic disease ecology and (2) diseases of commercial species. Progress over the past 20-years has been made by only a small number of researchers and aquatic disease in New Zealand has not received much attention from the wider marine science community. In 2020, the aquaculture industry continues to grow, and disease remains a threat to the industry's viability. However, additional factors such as climate change, invasive species, and pollution, have emerged as future threats for aquatic disease in wild and farmed populations, which are currently understudied. Here, we provide a review of studies on aquatic disease ecology and commercial species carried out in New Zealand. We also present how climate change, pollution and invasive species could influence future aquatic disease dynamics and identify where future research effort is required to address knowledge gaps. The emergence of consequential aquatic diseases overseas highlights wider attention across marine science disciplines is needed to progress and diversify aquatic disease studies in New Zealand.